Demystifying science: insights on the challenges of science communication in Ghana - Antwi, Wilhelmina (Kansas State University, 2023)
Innovative solutions from science and technology have profoundly improved people’s quality of life, health, and economic advancement worldwide. Moreover, as Carl Sagan (1990) rightly said, we live in a society “exquisitely dependent on science and technology, in which hardly anyone knows anything about science and technology.” Science and communication reveal and connect the world to the unknown. Without building a bridge between these two fields, our world will be rife with misconceptions and false information about science-related solutions. Science communication provides an excellent avenue for embracing innovations; however, despite the current growth in scientific knowledge tailored toward solving problems in developing countries, public engagement with scientific studies is minimal. This thesis explored the perceived challenges of communicating science in Ghana using in-depth interviews and discourse analysis as a theoretical framework. The findings of the study suggest that the perceived challenges of communicating science in Ghana are related to (a) science communication as an economic luxury (b) culture, beliefs, and taboos as a filter for science communication, and (c) science communication as an enabler of systematic bias. Responding to RQ2, participants’ discourse was positioned around one dominant moment of science communication as a collaborative effort.
Keywords: Science communication; Ghana; Developing country; Challenges; Intercultural communication; International communication